Urbanization and Urban Governance in China Issues, Challenges, and Development (Governing China in the 21st Century, 2018)
This book explores the process of urbanization and the profound challenges to China's urban governance. Economic productivity continues to rise, with increasingly uneven distribution of prosperity and accumulation of wealth. The emergence of individual autonomy including demands for more freedom and participation in the governing process has asked for a change of the traditional top-down control system. The vertical devolution between the central and local states and horizontal competition among local governments produced an uneasy political dynamics in Chinese cities. Many existing publications analyze the urban transformation in China but few focuses on the governance challenges. It is critical to investigate China's urbanization, paying special attention to its challenges to urban governance. This edited volume fills this gap by organizing ten chapters of distinctive urban development and governance issues. .